(untitled) (Stato, Chiese e pluralismo confessionale, 2014)
Contributo sottoposto a valutazione. Il contributo è destinato alla pubblicazione nel volume degli Atti del Corso di formazione giuridica in materia di pari opportunità e violazione del divieto di discriminazione di genere, organizzato dal Comitato Pari Opportunità presso il Consiglio dell’Ordine degli Avvocati di Napoli, ottobre 2013- giugno 2014 SOMMARIO: 1. I reati culturalmente motivati e il tentato omicidio per causa di “onore” - 2. Il concetto di onore nella cultura e nella tradizione giuridica dei Paesi mussulmani - 3. L’aggravante dei futili motivi nel nostro sistema penale - 4. Considerazioni conclusive. ABSTRACT The crime of honor and the aggravating factor of the trivial reasons’ culturally (and religiously) motivated A recent case law of the Italian Court of Cassation, on 2013, ruled that, in the case of the attempted murder of a daughter, trivial reasons cannot be considered based on the honor of the family and the violation of a fundamental religious precept. The evaluation of these cases then relates to that, of a much broader scope, linked to the concept of ’cultural crimes’ or cultural defence. It is necessary, however, to perform a careful balancing between guilt and offensiveness proportion on the one hand and, on the other hand, to consider the extent to which the author of a culturally motivated crime can enjoy a punitive treatment, though attenuated compared to those who commit the same crime without a cultural motivation. A judgment intrinsically linked to a cultural and ethical relativism, cannot be accepted that though respecting the multiculturalism of the western society in general, and of the Italian one in particular, must always find its legitimacy by submitting to the principles and values on which the Italian Constitution is founded.